علاقة الوالي برئيس المجلس الشعبي البلدي - هالة بوشوك; مريم راشدي (My University, 2015)
Summary: In this memorandum, we have presented the Wali's relationship with the Municipal People's Council, the most important of which is the Municipal Code 11-10 and the amendments it has made. These amendments are as follows: Defining the powers and powers of those elected to municipal councils, the role of the President of the Municipal People's Assembly, its deputies and municipal people's assembly committees. It also provides full protection for the electorate, which is further enhanced by the President's decisions to decriminalize acts of conduct. Perhaps one of the most important amendments to the essence of the law is the repeal of article 55 of Law 90 - 08, which provides for a recall procedure. In this Act, the legislator enshrined two constitutional principles contained in articles 16 and 31 bis of the Amendment. The Constitution of 2008 is the citizen's participation in the conduct of his municipal affairs, and the same is the promotion of women's rights by expanding their chances of representation in elected councils. ................................. الملخص : عرضنا في ثنايا هذه المذكرة علاقة الوالي بالمجلس الشعبي البلدي، و أهم ما جاء به قانون البلدية 11 – 10 و التعديلات التي جاء بها، و تتمثل هذه التعديلات في: تحديد صلاحيات و سلطات المنتخبين في المجالس البلدية، و دور رئيس المجلس الشعبي البلدي، و كذا نوابه و لجان المجلس الشعبي البلدي. كما يوفر حماية تامة للمنتخبين، و ما يعزز هذه الحماية بصفة أكثر هو القرارات التي اتخذها رئيس الجمهورية، و الخاصة برفع التجريم عن أفعال التسيير. و لعل من أهم التعديلات التي مست جوهر القانون هو إلغاء المادة 55 من القانون 90 – 08 و التي تنص على إجراء سحب الثقة. و كرس المشرع في هذا القانون مبدأين دستوريين تضمنتهما المادتين 16 و 31 مكرر من التعديل الدستوري 2008 ، و هو مشاركة المواطن في تسيير شؤون بلديته ، و كذا ترقية حقوق المرأة من خلال توسيع حظوظ تمثيلها في المجالس المنتخبة . ............................... Résumé : Dans ce mémorandum, nous avons présenté les relations du wali avec le Conseil municipal du peuple, dont la plus importante est le Code municipal 11-10 et les modifications qu’il a apportées. Ces modifications sont les suivantes : Définir les pouvoirs et les attributions des élus aux conseils municipaux, le rôle du président de l’assemblée populaire municipale, ses députés et les comités de l’assemblée populaire municipale. Il assure également une protection totale de l’électorat, renforcée par les décisions du président de décriminaliser les actes. Peut-être l’une des modifications les plus importantes à l’essence de la loi est l’abrogation de l’article 55 de la loi 90 - 08, qui prévoit une procédure de rappel. Dans cette loi, le législateur a inscrit deux principes constitutionnels contenus aux articles 16 et 31 bis de l’amendement. La Constitution de 2008 est la participation du citoyen à la conduite des affaires municipales, et la même chose est la promotion des droits des femmes en élargissant leurs chances de représentation dans les conseils élus.